2007
DOI: 10.4269/ajtmh.2007.76.549
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Enteric Protozoa in Human Immunodeficiency Virus (Hiv)–positive and Hiv-Negative Men Who Have Sex With Men From Sydney, Australia

Abstract: A prospective, comparative study of the prevalence of enteric protozoa was determined among human immunodeficiency virus (HIV)- positive and HIV-negative men who have sex with men (MSM) in Sydney, Australia. A total of 1,868 patients submitted stool specimens; 1,246 were from MSM (628 HIV positive and 618 HIV positive) and 622 from non-MSM were examined over a 36-month period. A total of 651 (52.2%) stool specimens from MSM were positive for protozoa compared with 85 (13%) from non-MSM. There was a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 32 publications
1
75
1
1
Order By: Relevance
“…Recent reports from a number of these coun-tries, however, suggest that invasive amebiasis is emerging as an increasingly common infection, specifi cally in the MSM population (2-6). MSM have a higher risk than others for intestinal parasite carriage; not only are they substantially more likely to harbor intestinal protozoa, but they are also more likely to harbor multiple parasites (11). These protozoa are transmitted by the fecal-oral route; high rates of oral-anal sex by MSM are considered the reason for increased rates of carriage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from a number of these coun-tries, however, suggest that invasive amebiasis is emerging as an increasingly common infection, specifi cally in the MSM population (2-6). MSM have a higher risk than others for intestinal parasite carriage; not only are they substantially more likely to harbor intestinal protozoa, but they are also more likely to harbor multiple parasites (11). These protozoa are transmitted by the fecal-oral route; high rates of oral-anal sex by MSM are considered the reason for increased rates of carriage.…”
Section: Discussionmentioning
confidence: 99%
“…2,30,31 This is supported by a recent prospective, comparative study comparing the prevalence of enteric protozoa among HIVpositive and HIV-negative men in Australia. 2,32 A total of 1,868 inpatients submitted stool specimens over a 36-month period to determine the presence of enteric parasites. 2 In this study C. parvum cases occurred exclusively in HIV-positive patients.…”
Section: Agholi Hatam and Motazedianmentioning
confidence: 99%
“…15 A study from Sydney showed high rates of intestinal parasites in MSM, with 52.2% of stool specimens positive for protozoa, compared with 13% from non-MSM, of which E. histolytica had a prevalence rate of 0.24% in the MSM group. 16 Another report of five cases of invasive amebiasis in MSM from Sydney further documents its existence in this at risk group. 17 Accurate prevalence and incidence data for E. histolytica are difficult to ascertain by microscopy alone, because it is morphologically indistinguishable, yet genetically distinct from non-pathogenic amoebic species; including Entamoeba dispar and Entamoeba moshkovskii .…”
mentioning
confidence: 99%